2021
DOI: 10.1177/0971355720974819
|View full text |Cite
|
Sign up to set email alerts
|

Economic Policy Uncertainty and Entrepreneurship: A Bad for a Good?

Abstract: The study examines the influences of the global/domestic economic policy uncertainty (EPU) on entrepreneurship in a sample of 23 economies over the period 2006–2016. Employing the two-step system General Method of Moment estimation for unbalanced panel data, our study provides surprising evidence, indicating that EPU may not always be harmful to entrepreneurship. Precisely, in contrast with existing literature emphasising the negative impact of the uncertainty on entrepreneurship, our article suggests that EPU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 56 publications
(54 reference statements)
1
15
2
Order By: Relevance
“…Based on digital technologies such as the internet and big data, digital inclusive finance simplifies the flow of information, expands the scope and depth of financial services, helps rural families obtain necessary start-up capital, reduces financing constraints (Geng & He, 2021), improves the profit space of entrepreneurs, and enhances their entrepreneurial willingness, thus equalizing entrepreneurial opportunities and promoting entrepreneurship (Liu et al, 2021). Nguyen et al (2021) also conclude that economic policy uncertainty is conducive to promoting entrepreneurial actions. As an economic policy, the contribution of digital inclusive finance to entrepreneurial behavior can also be seen.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Based on digital technologies such as the internet and big data, digital inclusive finance simplifies the flow of information, expands the scope and depth of financial services, helps rural families obtain necessary start-up capital, reduces financing constraints (Geng & He, 2021), improves the profit space of entrepreneurs, and enhances their entrepreneurial willingness, thus equalizing entrepreneurial opportunities and promoting entrepreneurship (Liu et al, 2021). Nguyen et al (2021) also conclude that economic policy uncertainty is conducive to promoting entrepreneurial actions. As an economic policy, the contribution of digital inclusive finance to entrepreneurial behavior can also be seen.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Recent studies have found that EPU also influences entrepreneurship significantly. The research of Nguyen et al [35] shows that EPU may not always be harmful to entrepreneurship. In the case of uncertainty, the reduction of the number of registered companies does not necessarily mean avoiding starting a business.…”
Section: Hypothesis 1 (H1) Entrepreneurship Can Promote Economic Deve...mentioning
confidence: 99%
“…EPU, which can be defined as the nonzero probability of changes in existing policies (Baker et al, 2016), has been shown to have adverse effects on various economic and financial fundamentals (Bernanke, 1983; Julio & Yook, 2012; Paule-Vianez, Prado-Román, et al, 2021). However, the direct relationship between EPU and entrepreneurship has hardly been investigated in the literature (Nguyen et al, 2021), although institutions and uncertainty are two vital concepts in the study of entrepreneurial activity (Bylund & McCaffrey, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%